Learning Environmental Ethics from "Sebuah Wilayah yang Tidak Ada di Google Earth" by Pandu Hamzah - Puspasari, Rahastri Fajar; Wiyatmi, Wiyatmi (Journal of Language and Literature, 2020)
This study aims to describe (1) the manifestations of environmental wisdom and (2) the role of the characters in environmental preservation contained in the novel Sebuah Wilayah yang Tidak Ada di Google Earth by Pandu Hamzah. This research is included in the type of descriptive qualitative research. The data source of this research is the novel Sebuah Wilayah yang Tidak Ada di Google Earth by Pandu Hamzah published by Literati in 2015. This research is focused on the manifestation of environmental wisdom and the role of characters in the novel by using ecocritical analysis. The data collection techniques are the technique of reading and taking notes. The data analysis technique used is descriptive qualitative. The validity of the data is obtained through semantic validity and intrarater reliability tests. The data were analyzed with description, categorization, and data presentation. The results of the study indicate the following matters. First, the manifestation of environmental wisdom found in the novel includes nine principles of environmental ethics, including (1) respect for nature; (2) the attitude of responsibility towards nature; (3) cosmic solidarity; (4) the principle of compassion and care for nature; (5) the principle of no harm; (6) the principle of living simply and in harmony with nature; (7) the principle of justice; (8) democratic principles; and (9) the principle of moral integrity. Among these principles, the most dominant principle is the principle of respect for nature. Second, the role of the characters in environmental preservation contained in the novel is divided into two categories, namely the role of pro-environment and non pro-environment.